If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(-5x + 7) = 56 Reorder the terms: -7(7 + -5x) = 56 (7 * -7 + -5x * -7) = 56 (-49 + 35x) = 56 Solving -49 + 35x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + 35x = 56 + 49 Combine like terms: -49 + 49 = 0 0 + 35x = 56 + 49 35x = 56 + 49 Combine like terms: 56 + 49 = 105 35x = 105 Divide each side by '35'. x = 3 Simplifying x = 3
| -3*3-9(3)= | | 2(-x+3)+5= | | -4x+172=6x+20 | | 2x-5/2=3x/2 | | -3(-8k+1)=45 | | -4(1+2x)=84 | | -9*(-45)+5y=-45 | | 7(2+4x)=238 | | 5c=78 | | 2(6x+5)=94 | | x+8(x+2)=5-x | | 192/-12 | | -9x+5*(-45)=-45 | | 4x-1(x-1)=-(x-1)+3x | | 2(3x-5)+x=12x-41solve | | a/2+a/3+a/4 | | 1/2*1/3 | | 3(6-x)=12 | | 1+z=2 | | 5w+10=5+8w | | -5(4x-8)=200 | | 2(6x+5)=154 | | 7(1-x)=4x+40 | | 192/-64 | | H+3.8=12.9 | | 6+v/-3=-2/3 | | 5/4x+1/8x=5/8+x | | 8m+9=6m+19 | | -7/5y=-35 | | 7+1/7l=-2 | | -45=-9x+5 | | 26n+17=-42 |